Societal Alienation Analysis in Chuck Palahniuk Novel “Fight Club” - Razak, Muhammad Fauzi; Riskiawati, Nur Sapta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the types of societal alienation displayed through main character in the 1996 novel